Increasing the safety of the transport process by minimizing the professional risk of a dump truck driver - Tsopa, Vitaliy; Cheberiachko, Serhii; Yavorska, Olena; Deryugin, Oleg; Bas, Ivan (Mining of Mineral Deposits, 2022)
Purpose.The aim of the study is to develop recommendations for reducing the probability of accidents during the transportation of rock by dump trucks based on the analysis of the consequences of changes in the psycho-physiological states of the driver. Methods. The study used the method of “Hazard and operability studies” and the method of “Failure Mode and Effects Analysis” including the organizational, logical and mathematical, and statistical procedures aimed at obtaining the expert assessment of hazards from professional experts based on Grabs’ criteria that affect to change the psychophysiological state of the driver while driving a dump truck, their analysis and generalization of the results in order to prepare reasonable decisions. Findings. It is established that the psychophysiological state of the driver as a manifestation of fear, anxiety, doubt, uncertainty when performing discrete work, which is associated with frequent changes in the beginning of movement and stops of the vehicle (accumulation of a large number of dump trucks, complex route plan, etc.) leads to an increase in the risk of an emergency. It is determined that the highest level of emergency occurs due to emotional manifestations, that are associated with the relationship between employees, the presence of leadership support, psychological assistance, mobbing, conflict resolution and more. Recommendations have been developed to increase the level of transportation safety through the formation of an appropriate organizational culture at the enterprise, which ultimately shapes human social behaviour. Originality. The scientific novelty lies in the establishment of the values of occupational risk of an accident while driving a dump truck by the driver, which depends not only on the probability of a dangerous event and the severity of its consequences, but also on changes in the psychophysiological state of the driver, which results from the organizational culture of occupational safety at the mining enterprise. Practical implications. Consists in the development of a procedure for qualitative assessment of the risk of an accident from the psychophysiological state of the driver during the trucking of rock in the conditions of the mining enterprise. Recommendations for improving the safety of transportation through the formation of an appropriate organizational culture of the transport process are developed. An approach of taking into account the socio-psychological climate in the organization to assess the occurrence of the incident is proposed.